2011
DOI: 10.1007/s12070-011-0311-x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Septal Deviation and External Nasal Deformity: A Correlative Study of 100 Cases

Abstract: A prospective study of 100 consecutive patients of deviated nasal septum to analyze association of septal deviation with external nasal deformity was undertaken at Acharya Vinoba Bhave rural Hospital of Jawaharlal Nehru Medical College, Sawangi (Meghe) Wardha from January 2009 to September 2010. Nasal septal deviations were evaluated by clinical examination and diagnostic nasal endoscopy while external nasal deformities, after evaluating, were documented using high resolution photography Nasal septal deviation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 10 publications
2
36
0
1
Order By: Relevance
“…In various other studies, mean age of 34.7 years, 33.5 years has been reported. 2,10 These findings by different investigators are in keeping with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In various other studies, mean age of 34.7 years, 33.5 years has been reported. 2,10 These findings by different investigators are in keeping with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to our findings, Sam et al found type VII (29%) as the most common septal deviation. 2 In another study conducted by Janardhan et al found Type V (45%), as the most common septal deviation. 11 In our study the least common type of deviation was type VI.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations